An Analysis of Gifted Students’ Adoption of Human Values - Şule Demirel Dingeç (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
Gifted students differ from their peers with regard to some of their characteristics, which may affect their needs as well. This study aims to determine the extent human values are adopted by gifted students. Survey was used as the method in the study. 48 secondary school students attending the Gifted Education Application and Research Center (UYEP) participated in the study. The level of human value adoption was determined with the Moral Maturity Scale developed by Dilmaç (1999). Existence of any gender- and grade-based differences were examined by performing direct difference analyses. The results of the study revealed that the human value adoption levels of gifted students are high, but they do not differ by grade and gender. It may be helpful to teach gifted students with strong human value adoption through curriculums that allow them to reflect these values in their lives.